Mechanical Far Lateral Disc Herniation Reproduction in Ovine Model for Intervertebral Disc Repair. (May 2014) - Friedmann, A.; Goehre, F.; Schwan, S.; Wiesner, I.; Meisel, H. J.
Introduction: Until today, the therapy of intervertebral disc disease is mainly based on the surgical removal of the cartilage tissue that protrudes between the vertebras, as well as the fixation of the vertebral bodies. Thus, the development of regenerative therapies for intervertebral disc degeneration presents a particular research area, which includes both material research and tissue engineering subjects. From a clinical point of view, it is assumed that a self-regenerative implant-based adipose mesenchymal stem cells, combined with an injectable scaffold material, represents a crucial improvement of the mechanical long-term stability of damaged intervertebral disc segments. The objective of the development, evaluation, and testing of the research is to examine various new materials in significant large animal model at several time stages. Materials and Methods: Because of the similarity in anatomy and biomechanics of the ovine intervertebral disc in comparison to human discs, the sheep animal model was selected. The disc herniation reproduction was performed through a minimal invasive surgery under X-ray control by penetration of the annulus fibrosis with subsequent removal of nucleus pulposus tissue with a Rongeur instrument. After 6 weeks, the induced degeneration of the disc could be observed. This represents the starting point for investigations of suitable materials for intervertebral disc implants. Our study is focused on the development of injectable hydrogels loaded with autologous adipose stem cells. Results: This model has been used successfully in 33 sheep for injectable scaffold material tests. The procedure and its implication will be presented based on X-ray and micro computed tomography imaging as well as analysis of the disc height. Conclusion: In cooperation with the BG Hospital Bergmannstrost Halle and Translational Centre for Regenerative Medicine (TRM) Leipzig we developed a suitable sheep animal model with a mechanically induced far lateral disc lesion. Disclosure of Interest None declared